The eShel Spectrograph: A Radial-velocity Tool at the Wise Observatory. (27th April 2017) - Engel, M.; Shahaf, S.; Mazeh, T.
Abstract: The eShel, an off-the-shelf, fiber-fed echelle spectrograph ( R ≈ 10, 000 ), was installed on the 1 m telescope at the Wise observatory in Israel. We report the installation of the multi-order spectrograph, and describe our pipeline to extract stellar radial velocity from the obtained spectra. We also introduce a new algorithm—UNICOR, to remove radial-velocity systematics that can appear in some of the observed orders. We show that the system performance is close to the photon-noise limit for exposures with more than 10 7 counts, with a precision that can get better than 200 m s −1 for F–K stars, for which the eShel spectral response is optimal. This makes the eShel at Wise a useful tool for studying spectroscopic binaries brighter than m V = 11. We demonstrate this capability with orbital solutions of two binaries from projects being performed at Wise.